Cryptic Eimeria genotypes are common across the southern but not northern hemisphere. Issue 9 (August 2016) - Clark, Emily L.; Macdonald, Sarah E.; Thenmozhi, V.; Kundu, Krishnendu; Garg, Rajat; Kumar, Saroj; Ayoade, Simeon; Fornace, Kimberly M.; Jatau, Isa Danladi; Moftah, Abdalgader; Nolan, Matthew J.; Sudhakar, N.R.; et al.
Graphical abstract: Highlights: The seven Eimeria spp. recognised to infect chickens are present globally. Cryptic Eimeria operational taxonomic units (OTUs) are common in the southern but not northern hemisphere. Parasite population structure appears to vary between Eimeria spp. Abstract: The phylum Apicomplexa includes parasites of medical, zoonotic and veterinary significance. Understanding the global distribution and genetic diversity of these protozoa is of fundamental importance for efficient, robust and long-lasting methods of control. Eimeria spp. cause intestinal coccidiosis in all major livestock animals and are the most important parasites of domestic chickens in terms of both economic impact and animal welfare. Despite having significant negative impacts on the efficiency of food production, many fundamental questions relating to the global distribution and genetic variation of Eimeria spp. remain largely unanswered. Here, we provide the broadest map yet of Eimeria occurrence for domestic chickens, confirming that all the known species ( Eimeria acervulina, Eimeria brunetti, Eimeria maxima, Eimeria mitis, Eimeria necatrix, Eimeria praecox, Eimeria tenella ) are present in all six continents where chickens are found (including 21 countries). Analysis of 248 internal transcribed spacer sequences derived from 17 countries provided evidence of possible allopatric diversity for species such as E. tenella (FST values ⩽0.34) but not E. acervulina and E. mitis, and highlighted a trend towards widespread genetic variance. We found that three genetic variants described previously only in Australia and southern Africa (operational taxonomic units x, y and z) have a wide distribution across the southern, but not the northern hemisphere. While the drivers for such a polarised distribution of these operational taxonomic unit genotypes remains unclear, the occurrence of genetically variant Eimeria may pose a risk to food security and animal welfare in Europe and North America should these parasites spread to the northern hemisphere.